Genesis of Concept of Adolescence: An Interdisciplinary Approach - Dogra, Bharti (INDIAN EDUCATIONAL REVIEW, 2007)
Puberty is a physiological process, which is seen in all the societies. Adolescence is not a universal concept. Adolescence is not a monolithic universal experience. It differs in different societies. Adolescence, as a transition between childhood and adulthood, is an invention of industrial revolution. Adolescence in traditional societies was different than in a post-industrial society. An interdisciplinary approach is required to draw the insights of the various disciplines together to study the genesis of this process common to all human beings: that of growing up. The resources of many disciplines are required to disentangle the interacting historical, biological, psychological, and sociological forces. What does growing up, or ‘coming of age’, mean today? What did it mean in earlier times? By looking at individuals as social agents in the particular cultural setting to what extent ties to norms and values of past times have been severed and how has this affected the process of growing up.